2018
DOI: 10.1038/s41598-018-30915-7
|View full text |Cite
|
Sign up to set email alerts
|

Bare surface of gold nanoparticle induces inflammation through unfolding of plasma fibrinogen

Abstract: The surface of nanoparticles (NPs) get coated by a wide range of biomolecules, upon exposure to biological fluids. It is now being increasingly accepted that NPs with particular physiochemical properties have a capacity to induce conformational changes to proteins and therefore influence their biological fates, we hypothesized that the gold NP’s metal surface may also be involved in the observed Fg unfolding and inflammatory response. To mechanistically test this hypothesis, we probed the interaction of Fg wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…Thus, this suggests that the cleavage site would be readily available to thrombin and would support our spectrometric data highlighting a conformational change in fibrinogen, rather than its aggregation. This is also supported by literature demonstrating that nanoparticles indeed can affect fibrinogen conformation, [45][46][47][48][49][50] including iron oxide nanoparticles. [31] Accordingly, Zhang et al reported that UV-vis spectroscopy of bovine fibrinogen incubated with 10 nm γ-Fe 2 O 3 indicated a decrease in absorbance intensity in the peaks at 218 and 275 nm when compared to fibrinogen.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, this suggests that the cleavage site would be readily available to thrombin and would support our spectrometric data highlighting a conformational change in fibrinogen, rather than its aggregation. This is also supported by literature demonstrating that nanoparticles indeed can affect fibrinogen conformation, [45][46][47][48][49][50] including iron oxide nanoparticles. [31] Accordingly, Zhang et al reported that UV-vis spectroscopy of bovine fibrinogen incubated with 10 nm γ-Fe 2 O 3 indicated a decrease in absorbance intensity in the peaks at 218 and 275 nm when compared to fibrinogen.…”
Section: Discussionsupporting
confidence: 81%
“…Citrate‐stabilized GNPs do not activate inflammatory pathway in THP‐1 cells, and instead, negatively regulate the inflammatory process, by selectively targeting IL‐1‐dependent pathway (Kharazian et al, ). GNPs downregulate the IL‐1‐induced responses in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the large surface of curvature, despite surface coating with moieties like PEG, ultrasmall GNPs can have gaps that can be filled with blood proteins such as fibrinogen. As a result, smaller GNPs can contribute to an inflammatory response, due to their interactions with these proteins, highlighting the necessity for proper functionalization [91]. Another factor that impacts biodistribution is the surface charge, which can be controlled by various surface conjugations, such as with PEG [92,93].…”
Section: Intracellular Fate Of Gold Nanoparticles Based On Their Physmentioning
confidence: 99%